2020
DOI: 10.4314/ahs.v20i1.26
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of human fascioliasis and its relationship with anti-Fasciola IgG and liver enzymes as biomarkers of pathogenicity

Abstract: Background: Fascioliasis has never been considered a public health concern in Pakistan, although the increasing numbers of human cases reported in south Asia need a re-consideration in the country. The current study aimed to find the seroprevalence of human fascioliasis, associated risk factors and its relationship with liver enzymes as biomarkers of pathogenicity. Methods: The cross-sectional study was conducted in different districts of Punjab region from May 2014 to August 2016. A total of 546 respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Fifteen different helminth species were represented, and these included Ancylostoma duodenale, Ascaris lumbricoides, Brugia malayi, Clonorchis sinensis, Fasciola hepatica, Necator americanus, Onchocerca volvulus, Opisthorchis viverinni, Schistosoma species (including S. haematobium, japonicum, and mansoni), Strongyloides stercoralifigs, Taenia solium, Trichuris trichiura, and Wuchereria bancrofti. Schistosoma species were most represented (S. mansoni (26), S. japonicum (8), unspecified Schistosoma species (7), and S. haematobium (2)) and studied in 43 studies, followed by mixed helminths (12), Strongyloides stercoralis (9), and others (20). The 34 records that did not meet Downs and Black criteria of "fair" or better quality are reported in S1 Supplemental Table . The associations of helminths with each of the 7 categories of cardiometabolic diseases and risk factors are discussed in the following sections.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fifteen different helminth species were represented, and these included Ancylostoma duodenale, Ascaris lumbricoides, Brugia malayi, Clonorchis sinensis, Fasciola hepatica, Necator americanus, Onchocerca volvulus, Opisthorchis viverinni, Schistosoma species (including S. haematobium, japonicum, and mansoni), Strongyloides stercoralifigs, Taenia solium, Trichuris trichiura, and Wuchereria bancrofti. Schistosoma species were most represented (S. mansoni (26), S. japonicum (8), unspecified Schistosoma species (7), and S. haematobium (2)) and studied in 43 studies, followed by mixed helminths (12), Strongyloides stercoralis (9), and others (20). The 34 records that did not meet Downs and Black criteria of "fair" or better quality are reported in S1 Supplemental Table . The associations of helminths with each of the 7 categories of cardiometabolic diseases and risk factors are discussed in the following sections.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, studies investigating metabolic syndrome with non-schistosome helminth infections also reported similarly lower measures of metabolic syndrome-related parameters among infected individuals (n = 8) [16,17,47,58,59,63,65,69]. In contrast to the 22 total studies showing inverse associations between helminth infections and metabolic syndrome or parameters, 14 other studies showed no association [7,8,13,14,20,21,26,32,45,52,53,57,67,68]. These 14 studies included mostly human studies and investigated 4 Schistosoma, 4 mixed helminth, 3 Strongyloides, 1 Opisthorchis, 1 Fasciola, and 1 Ascaris infections.…”
Section: Helminths and Metabolic Syndromementioning
confidence: 97%
See 2 more Smart Citations
“…There are more papers: chronic HIV infection and health related quality of life in resource poor settings 13 ; cryptococcosis among HIV patients in sub-Saharan Africa 14 ; malnutrition amongst HIV adult patients 15 ; viral suppression and low attrition in healthy HIV-infected patients initiated on ART with CD4 above 500 cells/µL 16 ; acceptance and utilization of HIV testing among the youth 17 ; rabies in Kwazulu-Natal 18 ; and central line-related bloodstream infections 19 . There are papers on Stenotrophomonas species 20 ; risk factors for trachoma in Burundi 21 ; plasmid-mediated resistance genes and multidrug-resistant uropathogens 22 ; prevalence of plasmodium , leptospira and rickettsia 23 ; seroepidemiology of human fascioliasis 24 ; Parvovirus B19 DNA detection in HIV anemic patients 25 ; safety of vaccines used in routine immunization in Africa 26 and distribution of genes among uropathogenic Escherichia coli and antimicrobial resistance 27 .…”
mentioning
confidence: 99%